Sistemas eletrônicos de gerenciamento de documentos arquivísticos: um questionário para escolha, aplicação e avaliação - Leandro Ribeiro Negreiros (2007)
The purpose of this work was the elaboration of a questionnaire to be used by specialists and archivists during the selection, application and evaluation of an electronic archives system of document management. Archival history was visited as a way to discuss the moment of insertion and use of information technologies in archives. The archival methods were analyzed so that it could be made clear that the sprouting and use of documents produced in electronic media do not intervene radically with the archival practices. The automation of archives was discussed at two moments: 1 - from the most eminent literature in Portuguese language; and 2 - under the perspective of electronic system of archives documentmanagement selection and the stages of the automation process. An electronic system of archives document management is here defined as a tool that is capable to guarantee: the properties of archival documents; the fulfilment of the life cycle (or vital cycle) of documents; the impediment that these archival documents suffer alterations or be eliminated, except in previously determined situations; the inclusion of rigorous retention periods and security controls; the efficient organization of archival documentation according to the forecasts of a filing plan; the formation of a safe archival documents repository, containing documents which are needed for the activities and functions of the organizations; and, above all, the easiness of access to these produced archival documents. The requirements in the MoReq Specification were used as a base for the elaboration of the questionnaire. A multidisciplinary work was done, envolving specialists in archives administration, computer science andsoftware producers that analyzed, evaluated and suggested modifications in the questionnaire. They also discussed, through interviews, the process of archive automation. Multidisciplinarity, terminology, specificities of archives administration and computer science, as well as the questionnaire itself, as an instrument for aiding archive automation, are the main discussed topics.